Lumbosacral (myelo) meningoceles in dogs, related tethered cord syndrome, and their surgical management: review of the literature and clinical experience - Roynard, Patrick; Dewey, Curtis Wells (Frontiers in Veterinary Science, 2025)
Neural tube defects (NTDs) are a group of congenital malformations characterized by various levels of protrusions of meninges with or without nervous tissue through incomplete osseous coverage (cranium bifidum for the cranial forms and spina bifida for spinal meningoceles/myelomeningoceles [MCs/MMCs]), with associated dorsal midline cutaneous signs. Amongst a confusing vocabulary, spina bifida is both the term most used to refer to NTDs and the most common manifestation of NTDs, with a predilection for the lumbosacral area in screw-tail breeds. With the growing popularity of bulldogs, lumbosacral (LS) MCs/MMCs are increasingly encountered, and small animal practitioners should learn to recognize them. Clinical signs may include urinary and/or fecal incontinence, pelvic limb neurological deficits with bunny hopping (neurolocalization L4-caudal or subset), and cutaneous signs (swirl of hair and dimple); the combination of which is pathognomonic of these disorders in bulldog puppies. Since these malformations often trigger a tethered cord syndrome (TCS), neurological worsening is possible. While historically reported to be somewhat hopeless regarding neurological improvement, isolated case reports, small case series, and personal experience of the author indicates that post-operative improvement is possible. Review of the literature (14 cases) and personal surgical experience (9 cases) retrieved 23 canine cases of LS MC/MMC treated surgically with follow-up. Clinical presentation, diagnostic imaging findings (CT and MRI), and intra- and post-operative findings are discussed in this article, along with a detailed description of the surgical technique. Pelvic limb deficits improve post-surgically in most cases (14/17 [82%] cases with pre-operative deficits and follow-up ≥1 month) albeit sometimes only marginally. Urinary/fecal continence can improve also, although less frequently (10/21 [48%] at 1 month follow-up and 8/21 [38%] at ≥6 months).